Using Intravenous Inmunoglobulin in an Atypical Case of Lambert Eaton Síndrome. - Erélido Hernández Valero; Osbert Rodríguez Miranda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
A 48 year-old hypertensive, smoker patient who started presenting a generalized weakness, pait instability,visual disorders and uncontrolled blood pressure is presented. At physical examination quadriparesis and weakness extraocular muscles were found. A repetitive estimulation test of low frequency was performed among other lab tests that had compatlbility with gravis myasthenia which was treated and improved. After this, an acute worsening of the condition was found and was treated with intravenous inmunoglobulin which produce a signifcant quantitative improvement. Days after this the patient stated to have some other disorders and, Lambert Eaton myasthenic syndrome was suspected. An electromyography test with 30 Hz was performed proving it. In spite of suffering a Lambert Eaton myasthenic syndrome this patient presented an acute state making a crisis which was improved with the use of intravenous inmunoglobulin. This result make us consider the usage of this medication as a therapeutic option in similar cases.